Does bad governance cause armed conflict? - Yiew, Thian Hee; Habibullah, Muzafar Shah; Law, Siong Hook; Wan Ngah, Wan Azman Saini (Serials Publications, 2016)
The issue of governance and armed conflict has been debated in recent years. Economists recognized that good governance is central to achieving higher economic development and also ending conflict. In this study, we investigate the effect of governance on armed conflict in 80 selected developing economies for the period 1996-2013. Using Logit model, we determine the response of armed conflict on six measures of governance: voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, rule of law, and control of corruption in a panel setting. As control variables, we include polity, polity square, social polarization, population and rugged terrain in the model. Interestingly, our results strongly suggest that good governance does contribute to reduce armed conflict. All the governance indicators show significant and negative impact on armed conflict. Moreover, our results suggest that the dimension of political stability and absence of violence is the best governance tool to end armed conflict.